1974
DOI: 10.1073/pnas.71.5.1607
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Polydeoxythymidylate Sequences in the Genome of the Cellular Slime Mold, Dictyostelium discoideum

Abstract: Messenger RNA of the cellular slime mold, Dictyostelium discoideum, contains about equimolar amounts of two classes of poly (adenylic acid) [poly(A)]; one is about 25 nucleotides long and the second about 100 nucleotides long. At least half of the messenger RNA molecules contain one sequence each of poly(A)25 and poly(A)soo; both poly(A) sequences are located near the 3' end of messenger RNA, and the kinetics of their appearance on messenger RNA precursor indicates that poly(A)25 is added before poly(A)soo. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

1974
1974
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 28 publications
2
19
1
Order By: Relevance
“…Since previous work indicated that about half of the DNA is transcribed into mRNA (7), it appears that there is, on the average, one poly(dT)25 sequence in the Dictyostelium genome per mRNA encoded. Additional hybridization experiments showed that the poly(dT) sequences are interspersed throughout the genome, and not clustered in one region (23). Thus, it appears that most DNA sequences coding for mRNA terminate with a poly(dT) sequence, as is indicated schematically in Fig.…”
Section: Following Addition Of [3h]adenosine To Vegetative Cellsmentioning
confidence: 90%
See 3 more Smart Citations
“…Since previous work indicated that about half of the DNA is transcribed into mRNA (7), it appears that there is, on the average, one poly(dT)25 sequence in the Dictyostelium genome per mRNA encoded. Additional hybridization experiments showed that the poly(dT) sequences are interspersed throughout the genome, and not clustered in one region (23). Thus, it appears that most DNA sequences coding for mRNA terminate with a poly(dT) sequence, as is indicated schematically in Fig.…”
Section: Following Addition Of [3h]adenosine To Vegetative Cellsmentioning
confidence: 90%
“…The other class is very heterogeneous and contains some sequences migrating at about 6 S [poly(A),5o] which are larger than is found in mRNA, and also material smaller than that isolated from mRNA; possibly the intermediate (2-4S) sized material represents nascent, growing poly(A) chains. Based on calculations similar to those for mRNA, we conclude that each molecule of nuclear poly(A)-containing RNA (isolated from pulse-labeled cells) contains one sequence of poly-(A)25 while only one molecule in three contains a longer poly-(A) sequence (13,23).…”
Section: Synthesis Of Mrnamentioning
confidence: 99%
See 2 more Smart Citations
“…The length of this sequence varies from 200 nucleotides in mammalian cells [39] to about 150 in insects (Pieris brassicae [40]), 100-120 in plants (Phaseolus aureus [6]) and 50 -60 in lower eukaryotic organism (Saccharomyces cerevisae [4] , Dictyostelium disoideum [41]). We have found an electrophoretic mobility corresponding to 4.5 S for the poly(A) from Tetrahymena pyriformis nuclear and cytoplasmic mRNAs, which corresponds to a chain length of about 100 nucleotides assuming that the electrophoretic behaviour of poly(A) is similar to that of tRNA and 5-S rRNA of E. coli.…”
Section: Discussionmentioning
confidence: 99%